Performativitas Dan Makna Tari Piring Talam Sapinggan Dalam Acara Pentas Seni Sungai Durian, Padang Pariaman - Adinda Muthiara Putri; Andre Andre; Sania Alya Putri; Najwa Putri Indra; Ramadhani Al Ihsan; Yulianti Rasyid (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The Piring Talam Sapinggan Dance is a Minangkabau cultural heritage that combines traditional dance movements with extreme attractions such as stepping on glass and spitting fire. This article examines the performativity and meaning contained in the performance, starting from the dance movements to the closing attraction. This research was conducted through direct observation of performances that display artistic and symbolic aspects of each movement and attraction. The research results show that the Piring Talam Sapinggan Dance not only emphasizes the beauty of movement, but also symbolizes strength, courage and respect for traditional values. The attraction of stepping on glass and spitting fire at the end of the show strengthens the symbolism of physical strength and agility, while maintaining the unique tradition passed down from generation to generation.